Cervical Margin Relocation for Indirect Bonded Restorations: A Literature Review - Ayari, Naima; Grira, Ibtissem; Moussa, Anissa Ben (Clinical Medicine And Health Research Journal, 2023)
Large posterior defects located beneath the gingival tissues complicate the use of indirect bonded restorations. It probably invades the biological width, during rubber dam isolation, impression taking and adhesive procedures. This article proposes a literature review of a new minimally invasive technique known as cervical margin relocation which allows to relocate subgingival margin to supragingival level using an appropriate material. A literature search was conducted in the Medline/PubMed database following the main key words: “cervical margin relocation», «deep margin elevation”, “proximal box elevation”, “indirect restorations”, “adhesion”, “marginal adaptation”, “subgingival margin”. A total number of 44 articles were included. Based on the reviewed literature, it can be concluded that cervical margin relocation technique emerged as an interesting alternative to surgical crown lengthening. However, further research, scientific evidence and randomized clinical trials with longer follow-up results are needed to clarify essentially the longevity of this technique and its compatibility with periodontal tissues.